2012
DOI: 10.1093/ajae/aar091
|View full text |Cite
|
Sign up to set email alerts
|

Testing Day's Conjecture that More Nitrogen Decreases Crop Yield Skewness

Abstract: While controversy surrounds skewness attributes of typical yield distributions, a better understanding is important for agricultural policy assessment and for crop insurance rate setting. Day (1965) conjectured that crop yield skewness declines with an increase in low levels of nitrogen use, but higher levels have no effect. In a theoretical model based on the law of the minimum (von Liebig) technology, we find conditions under which Day's conjecture applies. Employing four experimental plot datasets, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 36 publications
5
19
0
Order By: Relevance
“…Despite several researchers finding evidence of nonzero skewness in crop distributions, no consensus has been reached regarding the underlying cause of the observed nonzero skewness in crop distributions (Harri et al., ; Hennessy, ). Researchers have sought to provide a rationale for the observed nonzero skewness in crop yield distributions and have developed several theories to explain nonzero skewness such as weather, cropping practices, geographic region, and resource availability (Du et al., ; Harri et al., ; Hennessy, ). Of these hypotheses, the hypothesis about resource availability is perhaps the best developed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite several researchers finding evidence of nonzero skewness in crop distributions, no consensus has been reached regarding the underlying cause of the observed nonzero skewness in crop distributions (Harri et al., ; Hennessy, ). Researchers have sought to provide a rationale for the observed nonzero skewness in crop yield distributions and have developed several theories to explain nonzero skewness such as weather, cropping practices, geographic region, and resource availability (Du et al., ; Harri et al., ; Hennessy, ). Of these hypotheses, the hypothesis about resource availability is perhaps the best developed.…”
Section: Introductionmentioning
confidence: 99%
“…Day showed that skewness decreased as the quantity of nitrogen applied to the crops increased. Recently, Hennessy () and Du et al () have extended Day's work to try to explain how fertilizer inputs impact crop yield distributions. Hennessy () argued that nonzero skewness found in yield distributions is associated with minimum quantities of a limiting resource such as fertilizer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The covariates z i (land quality) are IID from a truncated normal distribution N (200,15 2 ) on the interval [100,300]. The beta distribution for error and the non‐constant scaling factor false|zi|1/5 are included to introduce left skewness in corn yield distributions (Ker and Goodwin, ; Du et al ., ) and increasing yield variation as the historical yield increases (Tannura et al ., ). Based on this yield model, observed premiums are generated from y i = μ ( x i , z i )+ ζ i , where ζ i ∼ N (0,0.1 2 ) are measurement errors, the covariates x i (coverage rates) are IID from a uniform distribution on the discrete numbers (0.55,0.60,…,0.90,0.95) and the true premium price is μfalse(x,zfalse)=pmfalse(zfalse)+|z|1/5ϵ̲xzFfalse(wfalse|zfalse)dw by equation .…”
Section: Simulation Studiesmentioning
confidence: 99%